Immunogenicity and reactogenicity of inactivated SARS-CoV-2 vaccines in healthy adults - Wu, Yufei; Huang, Ping; Xu, Mingjie; Zhao, Qianqian; Xu, Yihui; Han, Shuyi; Li, Huanjie; Wang, Yunshan (Frontiers in Immunology, 2023)
Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is highly pathogenic to humans and has caused the ongoing coronavirus disease 2019 (COVID-19) pandemic. Vaccines are one of the efficient ways to prevent the viral infection. After COVID-19 vaccination, the monitoring of the dynamic change in neutralizing antibodies is necessary to determine booster requirements. Methods We estimated the effectiveness of the inactivated vaccines by monitoring dynamic SARS-CoV-2 neutralizing antibodies for over 2 years. Additionally, we also investigated the activation of T lymphocytes (CD3+ T cells) after three doses of the inactivated vaccine. Result The results showed that the rate of reduction of SARS-CoV-2 neutralizing antibody levels gradually showed after each booster dose. The IgG/IgM level at 9 months after the third vaccination were significantly higher than those at 6 months after the second dose (p<0.0001). The expression of CD25+T cell in 18–35 age group was significantly higher than that in the other groups. Nine months after the third dose (the time of last blood sample collection), the expression of CD25+T cell in the 18–35 age group was significantly higher than that at 6 months after the second dose. CD25+T cell in the 18-35 years old group was significantly higher than 6 months after the second vaccination. Conclusion CD25, a late activation marker of lymphocytes and high-activity memory T cell subgroup, exhibited higher levels at the later stages after vaccination. COVID-19 booster vaccination in older adults and regular testing of SARS-CoV-2 neutralizing antibodies are recommended. Booster doses should be administered if the antibody level falls below the 30% inhibition rate.